2013
DOI: 10.1111/irv.12203
|View full text |Cite
|
Sign up to set email alerts
|

Influenza outbreak control practices and the effectiveness of interventions in long‐term care facilities: a systematic review

Abstract: Summary Background Evaluation of influenza control measures frequently focuses on the efficacy of chemoprophylaxis and vaccination while the effectiveness of non-pharmaceutical interventions (NPI) receives less emphasis. While influenza control measures are frequently reported for individual outbreaks, there have been few efforts to characterize the real-world effectiveness of these interventions across outbreaks. Objectives To characterize influenza case and outbreak definitions and control measures report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 52 publications
4
56
0
6
Order By: Relevance
“…Nonpharmaceutical interventions, including face masks and hand hygiene, were not found to reduce the risk of infection in the household setting. This is consistent with other nonpharmaceutical intervention studies [34][35][36]. Our estimates of the effectiveness of trivalent influenza vaccine for sH1N1 and sH3N2 were consistent with findings reported elsewhere [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nonpharmaceutical interventions, including face masks and hand hygiene, were not found to reduce the risk of infection in the household setting. This is consistent with other nonpharmaceutical intervention studies [34][35][36]. Our estimates of the effectiveness of trivalent influenza vaccine for sH1N1 and sH3N2 were consistent with findings reported elsewhere [18].…”
Section: Discussionsupporting
confidence: 92%
“…This might be explained by children having more frequent and intense contacts with other household members on average, compared with adults [32]. Consistent with previous studies, we found that oseltamivir treatment within 2 days since onset was not associated with reduced viral shedding [3,11,33,34]. However, we also found that oseltamivir treatment was associated with a reduction in infectivity for sH1N1 but not for sH3N2.…”
Section: Discussionsupporting
confidence: 90%
“…Since prophylaxis with oseltamivir was given to all residents of the NH1, and was limited to residents exposed to influenza in NH2, and was not used in NH3 at all, the preventive pharmacological intervention could be an explanation for the shortest duration of the outbreak in NH1. This assumption is in agreement with the recently published systematic review on influenza outbreak control practices and the effectiveness of interventions in long-term care facilities, indicating that pharmacological control measures have the clearest reported protective effect [18]. A similar effect of oseltamivir treatment and prophylaxis on the reduction of influenza outbreak duration in residents of NHs has also been recently reported by Booy et al [19] and is further supported by other studies [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 90%
“…Darüber hinaus stellen sie aber auch eine mögliche Infektionsquelle für die von ihnen betreuten und oft vulnerablen Senioren dar, sodass sie sich auch zum Schutz ihrer Patienten impfen lassen sollten. Denn trotz der relativ hohen Impfquoten der Bewohner kommt es aufgrund der eingeschränk-ten Wirksamkeit der Influenzaimpfung bei älteren und immungeschwächten Personen immer wieder zu Influenzaausbrü-chen, die mitunter schwerwiegend verlaufen [15,16,18]. Verschiedene Studien belegen den positiven indirekten Effekt der Impfung des medizinischen Personals in Bezug auf Influenzaerkrankungen bei Pflegebedürftigen [19][20][21].…”
Section: Influenza Vaccination · Health Information · Nursing Home · unclassified